2007
DOI: 10.1111/j.1365-2516.2007.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic issues in sports for persons with haemophilia

Abstract: Persons with haemophilia should not feel limited in their ability to participate in sports. After consultation with a physician or other health-care provider and with a proper understanding of the risks involved and the strategies for managing these risks, patients with haemophilia can - and should - enjoy physical activities. We have analysed numerous reports of sports injury statistics and used them to rank a variety of sports according to their degree of injury risk. In addition, we have developed a brief o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 15 publications
0
50
0
8
Order By: Relevance
“…The highest risk of injury was reported for basketball, squash, luge/tobogganing, water-skiing, bodybuilding, wrestling, and basketball (10). Activities with a lower risk of injury may be more suitable for a patient with hemophilia.…”
Section: Appropriate Physical Activities For Patients With Hemophiliamentioning
confidence: 99%
See 4 more Smart Citations
“…The highest risk of injury was reported for basketball, squash, luge/tobogganing, water-skiing, bodybuilding, wrestling, and basketball (10). Activities with a lower risk of injury may be more suitable for a patient with hemophilia.…”
Section: Appropriate Physical Activities For Patients With Hemophiliamentioning
confidence: 99%
“…In a review of more than 5 million reported sports related injuries in 44 different athletic activities in well individuals, the activities least associated with risk of injury included water polo, walking, cross country skiing, golf and swimming (10). The highest risk of injury was reported for basketball, squash, luge/tobogganing, water-skiing, bodybuilding, wrestling, and basketball (10).…”
Section: Appropriate Physical Activities For Patients With Hemophiliamentioning
confidence: 99%
See 3 more Smart Citations